Polyolefin breathable microporous film and preparation method thereof
By vinyl silane surface treatment of titanium dioxide, modified inorganic fillers were prepared and combined with polyolefin substrates to make a polyolefin breathable microporous film, which solved the problem of uneven dispersion of calcium carbonate particles in the resin and realized the film uniform structure and excellent breathability and mechanical properties.
Patent Information
- Application Number
- CN202411743785.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-30
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-30
AI Technical Summary
The calcium carbonate particles used in the pore making process of existing microporous breathable membranes are difficult to disperse evenly in the resin, resulting in a mess in the overall structure of the film.
The surface treatment of titanium dioxide was prepared by vinyl silane, and modified inorganic filler was prepared. The modified inorganic filler was mixed with a polyolefin substrate and casting extrusion, stretching and heat setting processes were carried out to make polyolefin breathable micropores. film.
Modified inorganic fillers have good dispersion and compatibility in polyolefin substrates, forming a uniform and small pore structure, improving breathability and water permeability, and enhancing the overall performance of the material, such as hardness, strength and resistance. Abrasive.
Smart Images

Figure BDA0005163129540000031 
Figure BDA0005163129540000041 
Figure BDA0005163129540000042
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of organic polymer films, and more specifically, to a polyolefin breathable microporous film and a preparation method thereof. Background Art
[0002] Microporous breathable film is a plastic film with numerous interconnected micropores. This film has high tensile strength, good permeability or breathability to air and water vapor, but has high hydrostatic pressure resistance to the penetration of liquid water, that is, this polyolefin breathable microporous film includes many openings or channels that can pass from one surface to another, and the size of the pores can allow air and water vapor molecules to pass through the film, while having good resistance to the penetration of liquid water molecules.
[0003] In the current production process of microporous breathable membranes, calcium carbonate is the most common pore-forming additive. However, due to the surface properties of calcium carbonate particles, they are often difficult to disperse evenly in the resin, making the overall structure of the microporous breathable membrane messy. Summary of the invention
[0004] In order to improve the uniformity of the overall structure of a microporous breathable membrane, the present application provides a polyolefin breathable microporous film and a preparation method thereof.
[0005] In a first aspect, the present application provides a polyolefin breathable microporous film, which adopts the following technical solution: A polyolefin breathable microporous film is made by filling a polyolefin substrate with a modified inorganic filler and undergoing a process of cast extrusion, stretching, and heat setting to form a film; The weight ratio of the polyolefin substrate to the modified inorganic filler is 9:11 to 1:1; The preparation method of the modified inorganic filler is as follows: titanium dioxide, vinyl silane and water are stirred and mixed at 100-120° C. for 2-5 hours, filtered, and dried to obtain the modified inorganic filler.
[0006] By adopting the above technical solution, the surface of the inorganic filler is treated with vinyl silane, and the surface of the modified inorganic filler contains vinyl groups, has good dispersibility in the polyolefin substrate, can be evenly distributed in the polyolefin substrate and form a stable structure. Therefore, the excellent dispersibility of the modified inorganic filler helps to form uniform and fine pores in the polyolefin breathable microporous film, thereby improving the air permeability and water permeability of the polyolefin breathable microporous film.
[0007] Preferably, in the modified inorganic filler, the inorganic filler is composed of titanium dioxide and calcium carbonate mixed in a weight ratio of 13:7 to 1:1.
[0008] Preferably, in the modified inorganic filler, the particle size of the inorganic filler is 2 to 5 μm, and the particle size distribution is greater than or equal to 85%.
[0009] Titanium dioxide is a stable, non-toxic ultraviolet light absorber. It is stable, low-cost, easy to recycle, has good photocatalytic activity, strong light scattering, high tinting power, large hiding power, good whiteness, strong achromatic power, high refractive index, high chemical inertness, has excellent electrical and thermal properties, is non-toxic and harmless to the human body, and is widely used in photosensitive materials, photocatalysts, cosmetics, food packaging materials, ceramic additives, rubber, plastics, leather tanning, luxury car coatings, antibacterial finishing and anti-ultraviolet finishing of textiles and other fields.
[0010] By adopting the above technical solution and using titanium dioxide as a pore-forming additive, not only can the pore structure of the breathable membrane be improved, but also the overall performance of the material can be improved. For example, it can enhance the hardness, strength and wear resistance of the material, while improving the light resistance and weather resistance of the material, making it less prone to aging and discoloration.
[0011] At the same time, by adjusting the amount of titanium dioxide added and the size of the added particles, the pore structure and distribution of the breathable membrane can be precisely controlled. This controllability enables the breathable membrane to meet the specific requirements of different fields for performance such as air permeability, water permeability and strength.
[0012] Preferably, the weight ratio of the inorganic filler, vinyl silane and water is 1:(0.05-0.1):(2-5).
[0013] Preferably, the vinyl silane is vinyl trimethoxy silane.
[0014] By adopting the above technical solution, vinyl trimethoxysilane contains a vinyl functional group with an unsaturated double bond structure and three hydrolyzable methoxy groups, and has dual reactivity. By controlling the weight ratio of inorganic filler, vinyl silane and water, vinyl trimethoxysilane is hydrolyzed to form silanol, which is bonded to the hydroxyl group on the surface of the inorganic filler, thereby grafting the active vinyl functional group on the surface of the inorganic filler. In the high-temperature melt extrusion process, the polyolefin substrate and the modified inorganic filler with similar structure have good compatibility, which is conducive to obtaining a breathable membrane with uniform overall structure.
[0015] Preferably, the preparation method of the modified inorganic filler is: mixing the inorganic filler, vinyl silane, polyethylene glycol and water at 100-120° C. for 2-5 hours, filtering and drying to obtain the modified inorganic filler.
[0016] By adopting the above technical scheme, the inorganic filler is surface modified by using polyethylene glycol and vinyl silane, and the surface of the modified inorganic filler is evenly coated with a silane layer, which is beneficial to further improve the dispersibility and compatibility of the modified inorganic filler in the polyolefin substrate, and obtain a breathable film with a uniform finishing structure.
[0017] Preferably, the polyolefin substrate comprises one or both of metallocene polyethylene and linear low-density polyethylene.
[0018] Preferably, the polyolefin substrate is composed of a mixture of metallocene polyethylene and linear low-density polyethylene in a weight ratio of 3:2.
[0019] By adopting the above technical scheme, a specific proportion of metallocene polyethylene and linear low-density polyethylene are selected for melt blending, excellent processing performance is achieved, the overall structural uniformity of the obtained breathable film is good, and the anti-aging performance and anti-tearing performance are excellent.
[0020] In a second aspect, the present application provides a method for preparing a polyolefin breathable microporous film, using the following technical solution: A method for preparing a polyolefin breathable microporous film comprises the following steps: S1: mixing the polyolefin substrate and the modified inorganic filler, and then extruding and granulating to obtain composite particles; S2: After the composite particles are cast and extruded into a film, the film is stretched and heat-set to obtain a polyolefin breathable microporous film; the melt temperature of the composite particles during cast extrusion is 225-270°C; the film stretching ratio is 1.2-3.5; and the heat setting temperature is 60-85°C.
[0021] By adopting the above technical solution, the polyolefin substrate and the modified inorganic filler have good processing performance at 225-270°C, so that the modified inorganic filler is evenly distributed in the polyolefin substrate and has good compatibility. Then, by treating according to the above stretching ratio and heat setting temperature, a breathable film with uniform overall structure, excellent anti-aging performance and excellent anti-tearing performance can be obtained.
[0022] In summary, this application has the following beneficial effects: 1. Since the present application uses a vinyl silane coupling agent to treat the surface of titanium dioxide, the dispersibility and compatibility of titanium dioxide in the polyolefin substrate are improved, so that the titanium dioxide is evenly distributed in the breathable membrane to form a stable pore structure, which is beneficial to improving the overall uniformity of the breathable membrane; 2. In this application, the pore distribution and pore structure in the breathable membrane can be adjusted by adjusting the amount of titanium dioxide added and the size of the added particles, which is conducive to expanding the application of the breathable membrane in different fields; 3. In the preparation method of the present application, under specific process conditions, the polyethylene substrate and the modified inorganic filler have good processing performance, and the preparation method is simple and suitable for large-scale production. DETAILED DESCRIPTION
[0023] The present application is further described in detail below in conjunction with embodiments.
[0024] Preparation Example Preparation Example 1 A modified inorganic filler, the raw materials and their corresponding weights (kg) are shown in the following table.
[0025] The preparation method of the modified inorganic filler is as follows: after mixing vinyl silane and water, adjust the pH value of the mixed solution to 3.5, mix for 45 minutes, then add the inorganic filler, mix at 120° C. for 2 hours, filter, dry, and crush to obtain the modified inorganic filler.
[0026] In the preparation examples of the present application, the vinyl silane is vinyl trimethoxy silane; The inorganic filler is composed of titanium dioxide SFA101 and calcium carbonate OM2-JI mixed in a weight ratio of 13:7; the particle size of the inorganic filler is 2-5 μm, and the particle size distribution is greater than or equal to 85%.
[0027] Preparation Examples 2-3 A modified inorganic filler, which is different from Preparation Example 1 in that the raw materials and their corresponding weights (kg) are shown in the following table.
[0028] Preparation Example 4 A modified inorganic filler, which is different from Preparation Example 1 in that the vinyl silane is vinyl triethoxy silane.
[0029] Preparation Example 5 A modified inorganic filler, which is different from Preparation Example 1 in that the inorganic filler is composed of titanium dioxide and calcium carbonate mixed in a weight ratio of 1:1.
[0030] Preparation Example 6 A modified inorganic filler, which is different from Preparation Example 1 in that the inorganic filler is composed of titanium dioxide and calcium carbonate mixed in a weight ratio of 2:5.
[0031] Preparation Example 7 A modified inorganic filler, which is different from Preparation Example 1 in that the raw materials and their corresponding weights (kg) are shown in the following table.
[0032] The preparation method of the modified inorganic filler is as follows: after mixing vinyl silane and water, adjust the pH value of the mixed solution to 3.5, mix for 45 minutes, then add the inorganic filler and polyethylene glycol 2000, mix at 120° C. for 2 hours, filter, dry, and crush to obtain the modified inorganic filler.
[0033] Preparation Example 8 A modified inorganic filler is different from Preparation Example 1 in that an equal weight of methyltrimethoxysilane is used to replace vinylsilane.
[0034] The preparation method of the modified inorganic filler is as follows: methyltrimethoxysilane and water are stirred and mixed for 45 minutes, then the inorganic filler is added, stirred and mixed at 120° C. for 2 hours, filtered, dried, and crushed to obtain the modified inorganic filler.
[0035] Performance Testing The porosity, pore size distribution, tensile strength, anti-aging performance and water permeability of the breathable microporous films prepared in the examples and comparative examples of the present application were tested as follows: Porosity and pore size distribution: tested in accordance with GB / T 21650.1-2008 standard.
[0036] Tensile strength: Refer to GB / T 1040.3-2006 Determination of tensile properties of plastics Part 3: Test conditions for films and sheets.
[0037] Anti-aging performance: refer to GB / T16585-1996 standard, carry out light aging test, and the aging time is set to 200h.
[0038] Water penetration rate: multiple squeeze penetration test method is used, the specific steps are as follows: Instruments: a 50ml measuring cup, several 2kg briquettes, a 1000ml beaker with a bottom area of 7*25cm, a stopwatch, several filter papers (with a minimum width greater than 200mm), several sanitary napkins, and several diversion tubes; Test solution: 23℃ normal saline (with a small amount of pigment), where the normal saline ratio is 9g sodium chloride per 1000ml distilled water; Sampling and sample preparation: The breathable microporous film should not have wrinkles or defects, and the sampling size should be larger than the area of the test sanitary napkin. The test sanitary napkin should remove the bottom film; Test steps: (1) Lay the filter paper flat on the platform; (2) Place the breathable microporous film to be tested on the filter paper, and then place the test sanitary napkin with the bottom film removed; (3) Inject 30 ml of the test solution into the center of the sanitary napkin through the flow guide tube; (4) After the liquid is completely absorbed, take a 2 kg block and press it on the sanitary napkin, and start the timer at the same time; (5) After 2 minutes, lift the block and press it down again. Repeat the above operation every 2 minutes. (6) After the fifth time of lifting the block, do not press it down any more and observe whether there is any leakage on the filter paper. If there is, it is determined that the batch of materials has permeation.
[0039] Five groups were tested in parallel, with 10 points in each group. Example
[0040] Example 1 A polyolefin breathable microporous film, the components and their corresponding weights (kg) are shown in the following table.
[0041] The method for preparing the above-mentioned polyolefin breathable microporous film comprises the following preparation steps: S1: mixing the polyolefin substrate and the modified inorganic filler, and then extruding and granulating to obtain composite particles; S2: Casting and extruding the composite particles to melt to form a melt, then extruding the melt into a film, and finally stretching and heat-setting the film to obtain a polyolefin breathable microporous film; The temperature of the melt was 225°C; the stretch ratio of the film was 1.2; and the heat setting temperature was 60°C.
[0042] In the embodiment of the present application, the polyolefin substrate is composed of a mixture of metallocene polyethylene and linear low-density polyethylene in a weight ratio of 3:2; The melt index of metallocene polyethylene is 3.5 g / 10 min and the density is 0.927; The melt index of linear low-density polyethylene is 2.3 g / 10 min and the density is 0.917; The modified inorganic filler is the modified inorganic filler prepared in Preparation Example 1.
[0043] Embodiment 2-3 A polyolefin breathable microporous film, which is different from Example 1 in that the components and their corresponding weights (kg) are shown in the following table.
[0044] The polyolefin breathable microporous films prepared in Examples 1 to 3 of the present application were tested for porosity, tensile strength, anti-aging performance and water permeability. The test results are shown below.
[0045] By analyzing the data in the above table, it can be seen that the polyolefin breathable microporous films prepared in Examples 1 to 3 have a porosity of up to 80 to 88%, a tensile strength of up to 12.70 to 13.60 N, and no yellowing occurs after 200 hours of light exposure, and no water seepage points. This shows that the polyolefin breathable microporous films prepared in Examples 1 to 3 of the present application have good overall structural uniformity, and excellent air permeability, mechanical properties, and anti-aging properties.
[0046] Embodiments 4 to 9 A polyolefin breathable microporous film, which is different from Example 1 in that the modified inorganic filler is a modified inorganic filler prepared by the preparation example in the following table.
[0047] The polyolefin breathable microporous films prepared in Examples 4 to 9 of the present application were tested for porosity, tensile strength, anti-aging performance and water permeability. The test results are shown below.
[0048] By analyzing the data in the above table, it can be seen that the porosity and tensile strength of Examples 4 and 5 are both reduced compared with Example 1. The reason may be that when the weight ratio of inorganic filler, vinyl silane and water is 1:0.08:3, the grafting effect of vinyl silane on the surface of inorganic filler is higher, which improves the dispersibility and compatibility of modified inorganic filler in polyolefin substrate, so not only the porosity of the film is improved, but also the overall uniformity of the obtained film is higher, so the mechanical properties are better.
[0049] Compared with Example 1, the porosity and tensile strength of Example 6 are both reduced. This shows that in the total raw materials for preparing the polyolefin breathable microporous film of the present application, surface modification of inorganic fillers using vinyltrimethoxysilane can improve the uniformity and mechanical strength of the overall structure of the film.
[0050] Compared with Example 1, the porosity and tensile strength of Examples 7 and 8 are both reduced. This shows that in the total raw materials for preparing the polyolefin breathable microporous film of the present application, adjusting the amount of titanium dioxide particles added can improve the overall air permeability and mechanical strength of the film.
[0051] Compared with Example 1, the porosity of Example 9 is reduced and the tensile strength is increased. This shows that in the total raw materials for preparing the polyolefin breathable microporous film of the present application, the surface modification of the inorganic filler by polyethylene glycol 2000 can improve the porosity and mechanical strength of the overall structure of the film. The reason for this may be that polyethylene glycol 2000 has good surface activity, which can promote the dispersion and grafting of silanol on the surface of the inorganic filler, further improving the dispersibility and compatibility of the modified inorganic filler and the polyolefin substrate.
[0052] Example 10 A polyolefin breathable microporous film, which is different from Example 1 in that the polyolefin substrate is composed of a mixture of metallocene polyethylene and linear low-density polyethylene in a weight ratio of 2:3.
[0053] The porosity and tensile strength of the polyolefin breathable microporous film prepared in Example 10 of the present application were tested, and the test results are shown below.
[0054] By analyzing the data in the above table, it can be seen that compared with Example 1, the porosity of Example 10 does not change much, but the tensile strength is significantly reduced. This shows that in the total raw materials for preparing the polyolefin breathable microporous film of the present application, the polyolefin substrate is composed of a mixture of metallocene polyethylene and linear low-density polyethylene in a weight ratio of 3:2, which can improve the porosity and mechanical strength of the polyolefin breathable microporous film.
[0055] Comparative Example Comparative Example 1 A polyolefin breathable microporous film, which is different from Example 1 in that the modified inorganic filler is the modified inorganic filler prepared in Preparation Example 8.
[0056] Comparative Example 2 A polyolefin breathable microporous film, which is different from Example 1 in that equal weights of inorganic filler and maleic anhydride grafted polyethylene (Article No. 24724, purchased from Dongguan Xingyuan Chemical Co., Ltd.) are used to replace the modified inorganic filler, wherein the weight ratio of the inorganic filler to the maleic anhydride grafted polyethylene is 1:0.1.
[0057] The polyolefin breathable microporous films prepared in Comparative Examples 1 to 2 of the present application were tested for porosity, tensile strength, anti-aging performance and water permeability, and the test results are shown below.
[0058] By analyzing the data in the above table, it can be seen that compared with Example 1, the porosity of Comparative Examples 1 and 2 is relatively reduced by 26.14-28.35%, the tensile strength is relatively reduced by 25.20-31.82%, and obvious yellowing occurs after 200 hours of illumination, and 3-5 water seepage points appear. This shows that in the total raw materials for preparing the polyolefin breathable microporous film of the present application, the surface modification of the inorganic filler using vinyl silane can improve the air permeability, mechanical strength, aging resistance and water seepage resistance of the polyolefin breathable microporous film.
[0059] At the same time, the polyolefin breathable microporous films prepared in Examples 1 to 10 of the present application and Comparative Examples 1 and 2 were subjected to pore size distribution and appearance tests. The test results show that the polyolefin breathable microporous films prepared in Examples 1 to 10 have a pore size distribution of 0.01 to 0.06 nm, high whiteness and gloss, and uniform overall structure. The polyolefin breathable microporous films prepared in Comparative Examples 1 and 2 have a pore size distribution of 0.04 to 0.26 nm, and their whiteness, gloss, and overall structural uniformity are lower than those of Examples 1 to 10. Therefore, the polyolefin breathable microporous film of the present application has a uniform overall structure, a narrow pore size distribution, high safety and whiteness and gloss, no leakage, high strength, and excellent aging resistance, and can be used in the use environment of sanitary products to improve the user experience.
[0060] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A polyolefin breathable microporous film, characterized in that: It is made of polyolefin substrate filled with modified inorganic filler, and is made through cast extrusion, stretching, and heat setting film forming processes; The weight ratio of the polyolefin substrate to the modified inorganic filler is 9:11 to 1:1; The preparation method of the modified inorganic filler is as follows: the inorganic filler, vinyl silane and water are stirred and mixed at 100-120° C. for 2-5 hours, filtered and dried to obtain the modified inorganic filler.
2. The polyolefin breathable microporous film according to claim 1, characterized in that: In the modified inorganic filler, the inorganic filler is composed of titanium dioxide and calcium carbonate mixed in a weight ratio of 13:7 to 1:
1.
3. The polyolefin breathable microporous film according to claim 1, characterized in that: In the modified inorganic filler, the particle size of the inorganic filler is 2-5 μm, and the particle size distribution is greater than or equal to 85%.
4. The polyolefin breathable microporous film according to claim 1, characterized in that: The weight ratio of the inorganic filler, vinyl silane and water is 1:(0.05-0.1):(2-5).
5. The polyolefin breathable microporous film according to claim 1, characterized in that: The vinyl silane is vinyl trimethoxy silane.
6. The polyolefin breathable microporous film according to claim 1, characterized in that: The preparation method of the modified inorganic filler is as follows: the inorganic filler, vinyl silane, polyethylene glycol and water are stirred and mixed at 100-120 DEG C for 2-5 hours, filtered and dried to obtain the modified inorganic filler.
7. The polyolefin breathable microporous film according to claim 1, characterized in that: The polyolefin substrate includes one or both of metallocene polyethylene and linear low-density polyethylene.
8. The polyolefin breathable microporous film according to claim 7, characterized in that: The polyolefin substrate is composed of metallocene polyethylene and linear low-density polyethylene mixed in a weight ratio of 3:
2.
9. The method for preparing the polyolefin breathable microporous film according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1: mixing the polyolefin substrate and the modified inorganic filler, and then extruding and granulating to obtain composite particles; S2: After the composite particles are cast and extruded into a film, the film is stretched and heat-set to obtain a polyolefin breathable microporous film; The melt temperature of the composite particles during cast extrusion is 225-270°C; the film stretching ratio is 1.2-3.5; and the heat setting temperature is 60-85°C.
Citation Information
Patent Citations
Composition of air-permeable film with low permeation volume and preparation method thereof
CN102336940A
Porous polyolefin film and preparation method thereof
CN112812340A
Microporous breathable film and method of making the microporous breathable film
US20170008211A1
Ultra-breathable polyolefin film material, and preparation method therefor
WO2024222833A1
Cited By
Breathable microporous polyolefin film and preparation method therefor
WO2026113277A1